ENVIRONMENTAL PERFORMANCE, INTELLECTUAL CAPITAL, PRAKTIK PENGHINDARAN PAJAK DAN NILAI PERUSAHAAN - EKA SEPTIANI; HOLIAWATI HOLIAWATI; ENDANG RUHIYAT (Jurnal Bisnis dan Akuntansi, 2019)
This study aims to examine the effect of environmental performance, intellectual capital and tax avoidance practices on firm values. This type of research is quantitative by using the population in this study is a manufacturing company that is listed on the Indonesia Stock Exchange in 2012-2016. The selection of data samples using a purposive sampling technique. The analytical method used is multiple linear regression analysis. The results of this study indicate that environmental performance has no effect on company values, intellectual capital has a positive and significant effect on corporate values and tax avoidance practices that have a negative and significant effect on firm value.